(untitled) (Global Journal of Human-Social Science, 2025)
In this paper making use of the observational data of Comets observed in Ancient and Mediaeval Korea we anew elucidated the observational history of the comet 2P Encke become well known up to now We found that out of comets corresponding to a few hundred observed in ancient and mediaeval Korea the observations of comets the periods of which was approximately 3 3year amount to 32 cased This means that the comet 2P Encke which had been discovered in AD 1786 in western world had been in AD 54 it had been already observed 32times in Korea up to AD 1638